Adjuvant Chemotherapy Using the FOLFOX Regimen in Colon Cancer - Jeon, Hyeong-Joon (The Korean Society of Coloproctology, 2011)
PURPOSE: Great progress has been made in the adjuvant treatment of colon cancer. The aim of this study was to evaluate the efficacy of postoperative adjuvant chemotherapy using the FOLFOX regimen in patients with stage III and high-risk stage II colon cancer. METHODS: Eighty-two patients who underwent a potentially curative resection for stage III or high-risk stage II colon cancer were enrolled in this retrospective study. They received FOLFOX4 or modified FOLFOX6. The primary endpoint was disease-free survival. RESULTS: During the median follow-up of 37 months (range, 21 to 61 months), 14 patients experienced disease relapse. The disease-free survival rate at 3 years was 82.9%: 84.6% for stage II and 82.6% for stage III. At the time of the analysis, 8 patients were dead from recurrence. The probability of overall survival at 5 years was 74.5%: 90% for stage II and 74.6% for stage III. Grade 3 or 4 hematologic adverse events included neutropenia (40.2%), anemia (2.4%), and thrombocytopenia (1.2%). Gastrointestinal toxicities included grade 3 or 4 nausea (4.9%) and stomatitis (2.4%). Peripheral sensory neuropathy was observed in 81.7% of the patients during treatment. Of the 11 patients (13.4%) who had grade 3 peripheral sensory neuropathy during treatment, grade 3 symptoms were persistent in 3 patients with gait disturbance at the time of analysis. No treatment-related deaths were recorded. CONCLUSION: Postoperative chemotherapy using the FOLFOX regimen, oxaliplatin in combination with 5-fluorouracil and leucovorin, is effective and tolerable in patients with stage III and high-risk stage II colon cancer.